The power of eLearning from promises to practices applied in engineering - PECA, Ludmila (Journal of Social Sciences)
Significant strides are being made in the development of Information and Communication Technology (ICT) by infusing ICT as a tool for learning and education. Expansive and visionary programs are initiated meant to transform university education. The latter have jointly contributed to the considerable progress of the renewed curricula development and implementation, including the hybrid learning model for a number of key courses such as mathematics, science, computer networks, programming and ICT. Sectoral digitalization is implemented due to the digitalization strategies and initiatives. Computer and science labs support e-learning and of course the training and retraining of the teaching staff for new curricula (study-programmes), new pedagogical methodologies and assessment strategies. In general terms, the study-programmes have been renewed/redesigned to become more relevant fulfilling students’ needs, while the specific outcomes are based less on knowledge and content and more on learning skills and competences, i.e. real-world applicable tasks/activities. The paper describes the study case of the presentation format for the Computer Networks course, which can be found in the study plan/syllabus of several study-programmes at the Faculty of Computers, Informatics and Microelectronics (FCIM) and the Faculty of Electronics and Telecommunications (FET) of the Technical University of Moldova (TUM).